PROFIL SISWA TUNAGRAHITA RINGAN (X) YANG BERPRESTASI DI BIDANG KETERAMPILAN MENJAHIT DI SLB NEGERI 1 HARAU - Adinda Fania; Asep Ahmad Sopandi (Jurnal Penelitian Pendidikan Khusus, 2023)
The purpose of this study was to find out the achievements of students with mental retardation X and anyone who has an active role in increasing the achievements achieved by X to excel in the sewing skill branch at the provincial level. This research uses a type of case study research. The subject of this research is a mentally retarded child who achieves achievements in sewing. The research was conducted at SLB N 1 Harau. Data collection techniques in this research are in the form of interviews and case studies. The results of this study are that X was able to achieve achievements in the field of sewing skills, namely in the LKSN PDBK event at the district, provincial and national levels. The role of the teacher in developing X's achievements is to provide moral support by providing motivation and guidance. The learning method given by Mrs. Ida Hamidah is by providing coaching, guidance and practice.